Indigenous Religions Strategy in Maintaining their Belief - Setiawan, Iwan; Goffary, Irfan; Hamim, Mohamad (UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this study is to discuss the patterns of strategy adherents of the Madrais or the Djawa Sunda Religion (ADS) in Cigugur, Indonesia, in maintaining their trust. This study uses a qualitative approach to the descriptive-analytic method through literature studies. Data obtained through the review of the literature and then analyzed using content analysis (content analysis) using Miles and Crow's theory of